Genome variation and evolution of the malaria parasite Plasmodium falciparum. - Jeffares, D; Pain, A; Berry, A; Cox, A; Stalker, J; Ingle, C; Thomas, A; Quail, M; Siebenthall, K; Uhlemann, A; Kyes, S; Krishna, S; et al. (2007)
Infections with the malaria parasite Plasmodium falciparum result in more than 1 million deaths each year worldwide. Deciphering the evolutionary history and genetic variation of P. falciparum is critical for understanding the evolution of drug resistance, identifying potential vaccine candidates and appreciating the effect of parasite variation on prevalence and severity of malaria in humans. Most studies of natural variation in P. falciparum have been either in depth over small genomic regions (up to the size of a small chromosome) or genome wide but only at low resolution. In an effort to complement these studies with genome-wide data, we undertook shotgun sequencing of a Ghanaian clinical isolate (with fivefold coverage), the IT laboratory isolate (with onefold coverage) and the chimpanzee parasite P. reichenowi (with twofold coverage). We compared these sequences with the fully sequenced P. falciparum 3D7 isolate genome. We describe the most salient features of P. falciparum polymorphism and adaptive evolution with relation to gene function, transcript and protein expression and cellular localization. This analysis uncovers the primary evolutionary changes that have occurred since the P. falciparum-P. reichenowi speciation and changes that are occurring within P. falciparum.